Effectiveness of the Kuningan Samsat Service: Responding to the Challenges of Productivity and Public Satisfaction - Khumayah, Siti; Salsabila, Adinda Salwa (Asian Journal of Social and Humanities, 2026)
The One-Stop Administration System (SAMSAT) is a public service institution that plays an important and strategic role in managing motor vehicle administration and interacts directly with the community. In carrying out its duties, this institution faces various operational challenges, including queue congestion at certain hours, disruptions in the application system, and a lack of behavioral consistency among officers. This study aims to analyze the effectiveness of SAMSAT Kuningan services based on the three dimensions of Richard M. Steers’ theory, namely productivity, community satisfaction, and adaptability, as well as to identify inhibiting factors and efforts to improve them. The method used is descriptive qualitative, with data collection techniques consisting of in-depth interviews, field observations, and document analysis. The results show that service productivity is relatively high because revenue realization almost entirely meets the target, with a large volume of vehicles served every day. Most people expressed satisfaction with the services received, which were generally categorized as good, although variations in user experience were still found. The adaptability aspect shows the progressive implementation of digital innovation; however, its utilization is not evenly distributed among the community. This study concludes that SAMSAT Kuningan services are generally effective but still require improvements in service consistency, the reliability of technological systems, and strengthened adaptation efforts to achieve full optimization.